2020
DOI: 10.3390/min10121100
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous Plume–Ridge Interaction Recorded in the Band-e-Zeyarat Ophiolite (North Makran, Iran): New Constraints from Petrological, Mineral Chemistry, and Geochronological Data

Abstract: The North Makran domain (southeast Iran) is part of the Makran accretionary wedge and consists of an imbricate stack of continental and Neo-Tethyan oceanic tectonic units. Among these, the Band-e-Zeyarat ophiolite consists of (from bottom to top): ultramafic cumulates, layered gabbros, isotropic gabbros, a sheeted dyke complex, and a volcanic sequence. Sheeted dykes and volcanic rocks are mainly represented by basalts and minor andesites and rhyolites showing either normal-type (N) or enriched-type (E) mid-oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
2
6
0
Order By: Relevance
“…Several distinct tectonic settings including rifted island-arcs, back-arc basins, and fore-arc basins, have been suggested for the origin of the SSZ ophiolite (Kusky 2004 Our previous 40 Ar/ 39 Ar ages of coarse-grained gabbro and hornblende gabbro from the KOC indicate an age of 152.7 ± 5.1 Ma and 126.5 ± 1.6 Ma, respectively. These ages are similar to reported K/Ar ages by Kananian et Barbero et al (2020a) (122 to 129 Ma), implying that plagiogranites probably formed simultaneous with or after formation of the oceanic crustal ma c rocks (121 to 156 Ma). We argue that plagiogranite rocks formed by partial melting of gabbroic rocks (Ghasemi Siani et al 2021a, b).…”
Section: Tectonic Setting Of Kocsupporting
confidence: 88%
See 2 more Smart Citations
“…Several distinct tectonic settings including rifted island-arcs, back-arc basins, and fore-arc basins, have been suggested for the origin of the SSZ ophiolite (Kusky 2004 Our previous 40 Ar/ 39 Ar ages of coarse-grained gabbro and hornblende gabbro from the KOC indicate an age of 152.7 ± 5.1 Ma and 126.5 ± 1.6 Ma, respectively. These ages are similar to reported K/Ar ages by Kananian et Barbero et al (2020a) (122 to 129 Ma), implying that plagiogranites probably formed simultaneous with or after formation of the oceanic crustal ma c rocks (121 to 156 Ma). We argue that plagiogranite rocks formed by partial melting of gabbroic rocks (Ghasemi Siani et al 2021a, b).…”
Section: Tectonic Setting Of Kocsupporting
confidence: 88%
“…Therefore, in this paper, we focus on whole-rock geochemistry of ma c and ultrama c rocks and Sr-Nd-Pb isotopic data. Our new results plus data from the literature (Kananian 2001;Ghazi et al 2004;Arvin et al 2005; Barbero et al 2020a) will assist in deciphering the petrogenesis and allow evaluation of the tectonic setting of KOC.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…All the analyzed clinopyroxenes show a negative correlation between Mg# and Ti apfu (Figure 11C). Clinopyroxene compositions are plotted in the TiO2-SiO2/100-Na2O ternary diagram [6,29], which correlates the mineral chemistry of clinopyroxene with the geodynamic formation setting (Figure 12A-F). The entire dataset shows a certain affinity with within Oceanic Plate basalts (WOPBs) and Iceland basalts (ICBs).…”
Section: Texture and Composition Of Clinopyroxenementioning
confidence: 99%
“…Similar to olivine, clinopyroxene appears in the early phase during the crystallization of mantle-derived magmas. Therefore, the composition of magmatic clinopyroxene in volcanic rocks records key information regarding the chemistry and evolution of the host lavas, the crystallization conditions, and the geodynamic settings in which the clinopyroxene and its host rock formed [4,6,27,29,30,55,76]. In particular, it has been suggested that the variation in clinopyroxene compositions can be related to differences in the primary composition of the parent magma rather than the physical conditions of crystallization [77].…”
Section: The Significance Of Clinopyroxene Compositionmentioning
confidence: 99%